XVIII International conference “Current Problems of Energy Conversion in Lithium Electrochemical Systems”, (Sochi (Sirius Federal Territory), October 7–12, 2024) - Skundin, Aleksandr Mordukhaevich; Kudryashova, Yuliya Olegovna (Электрохимическая энергетика)
-